Morphological adaptation of the alimentary canal of four Labeo species in relation to their food and feeding habits - Gupta, M Das (Indian Journal of Fisheries, 2011)
The structure and morphometries of the alimentary canal of four Labeo species(Labeo bata, L.calbasu, L.gonius, and L. rohita) have been described in relation totheir food and feeding habits. The general pattern of the alimentary canal wasfound to be similar and of herbivorous type in all the species. L. gonius was foundto be the most herbivorous among the four species studied, followed by L. rohitaand L. calbasu, the least herbivorous as indicated by the structure andmorphometries of the alimentary canal, nature of stomach contents and relativelength of the gut. The pattern of mucosal folds in the different regions of thealimentary canal showed intra and inter-specific variations.